Los catálogos de librería de las sociedades Anisson-Posuel y Arnaud-Borde conservados en la Biblioteca Histórica de la Universidad Complutense - Clemente San Román, Yolanda (Revista General de Información y Documentación, 2010)
The article offers a detailed study of the bookselling trade in Lyon and Paris in the second half of the seventeenth and in the early decades of the eigthteenth century, based on the catalogues of two societies of booksellers: the society of the Anisson brothers and Jean Posuel, and the society of Felipe and Pierre Borde with Lorenzo Arnaud. The catalogues are classified according to subject matter and through a list of the most relevant titles, and special emphasis is made on the offer of Spanish and Italian books.
Keywords: Bookselling trade; France; S; XVII-XVIII